Internalisasi Karakter Katolik Berbasis Communio untuk Mewujudkan Smart Student pada Sekolah Menengah Atas Katolik di Ruteng - Keristian Dahurandi; Emanuel Haru; Rikardus Moses Jehaut (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2023)
This paper aims to describe the form of internalization of Catholic character in Catholic High School as an effort for community literacy. The study used the qualitative method. Data were analyzed by collecting, reducing, display and drawing conclusions or verification. Data processing is assisted by Atlas.ti software version 9.0.15. The result show that the obstacles to internalize Catholic characters are inconducive environmental, lack of teachers modeling, low learning motivation of student, and negative impact of digital technology. The form of internalizing Catholic character in the High School context must be inspired by “Communio” paradigm of the Catholic church. The basic spirit of Communio is Bible reflection by reading and member’s sharing experience to each other. There are forth efforts to internalize Catholic character. The first, environmental design with Catholic Spiritual nuances. Second, the formation of small spiritual groups such as Bible sharing groups, catechesis, devotions, Bible reading and quizzes competitions, and pilgrimages to the Catholic Spiritual sites. Third, integration of Information Technology-based spiritual development such as used of e-Catholic applications, Bible catechism vlogs, catholicity website, and other prophetic software. Fourth, character Catholic internalization based on dormitory system. This method is chosen to compose the sustainable, integrative, collaborative, and systematic of Catholic character internalization. However, this research, is still limited to the High School context, so it has not examined other level of formal school context. In addition, this research is still limited to formal school managed by Catholic foundations and headed by Catholic priest, clergy and religious sisters.